ROMANIAN PENSION SYSTEMS AND LABOR SUPPLY OF OLDER WORKERS - Cristina CIURARU-ANDRICA (Management Intercultural, 2013)
Prolonging working lives, in the context of an ageing population, has been seen as a good way to improve, on the one hand, the financial sustainability of the public pension system and, on the other hand, the adequacy of the pension benefit. As the literature has shown, even when measures for extending working lives have been taken, the characteristics of the national pension system (especially those of public pension system) deliberately or inherently affected the labor market exit of older workers. Thus, through an econometric analysis, we estimate the relationship between the participation rate of Romanian older workers and certain characteristics of the Romanian pension systems (but not only), hoping to complement a more general literature on the effects of pension systems on retirement decision.